Values of Traditional Education Through the Procession of Mājar-ajar in the Hindu Community at Pura Agung Besakih - Sudiarta, I Nyoman; Artayasa, I Putu; Suda, I Ketut (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
This study aims to analyze the values ​​of traditional education contained in the Mājar-ajar procession and examine its implications for the Hindu community's social, cultural, and economic aspects in Bali. The research method used is qualitative with observation techniques, in-depth interviews, and literature studies. The results of the study indicate that the Mājar-ajar procession contains traditional educational values, such as the teachings of tatwa (Hindu philosophy), susila (morality), and ceremonies (religious rituals), which are passed down from generation to generation. From a social aspect, this procession strengthens social relations, solidarity, and a sense of togetherness in society. From a cultural aspect, this procession is a means of preserving Hindu traditions and cultural identity in Bali through ritual symbols, performing arts, and religious practices. Meanwhile, from an economic aspect, this procession contributes to the empowerment of the community's economy through the tourism sector, creative industry, and trade in ritual products. The Mājar-ajar procession functions as a religious ritual. It has a strategic role in maintaining the continuity of traditional education, strengthening social and cultural structures, and encouraging economic growth based on local culture. Therefore, efforts are needed to preserve and develop this procession to remain relevant and useful in Hindu society in Bali.